Towards Enabling Inclusive Conversations: Bridging Accessibility Gaps for the Visually Impaired in a Chatbot Web Chat - de Moraes, João Antônio Desidério; Silva, Geovana Ramos Sousa; Canedo, Edna Dias (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC), 2024)
Context: Web chats are widely used in corporate and social settings, making inclusivity in web-based communication platforms crucial. However, visually impaired individuals often encounter obstacles in digital conversations due to the dynamic nature of web chat elements, which poses challenges for screen reader compatibility. This paper addresses these challenges by adapting an open-source web chat designed for chatbot interactions to be fully compatible with screen readers. Our solution involves modifying the web chat’s code to enhance the user experience for visually impaired individuals. Key modifications include integrating semantic HTML tags, Accessible Rich Internet Applications (ARIA) landmarks, and other accessibility-focused techniques. We employed a combination of Proof of Concept and Experimentation, starting with an examination of the existing web chat, followed by the code modifications. Validation was conducted through execution and analysis of two use case scenarios. Results show significant improvements in user experience, as evidenced by screen reader transcriptions. Notable enhancements include improved navigation and the overall announcement of chat updates. This research contributes to Human Factors in Computing Systems by addressing web chat accessibility gaps. The adapted open-source web chat demonstrates the positive impact of minor code modifications on usability for users with visual impairments, exemplifying inclusive design in digital communication platforms.